2013
DOI: 10.3390/md11114127
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Studies of Marine Diterpenes as Inhibitors of Wild-Type and Mutants HIV-1 Reverse Transcriptase

Abstract: AIDS is a pandemic responsible for more than 35 million deaths. The emergence of resistant mutations due to drug use is the biggest cause of treatment failure. Marine organisms are sources of different molecules, some of which offer promising HIV-1 reverse transcriptase (RT) inhibitory activity, such as the diterpenes dolabelladienotriol (THD, IC50 = 16.5 µM), (6R)-6-hydroxydichotoma-3,14-diene-1,17-dial (HDD, IC50 = 10 µM) and (6R)-6-acetoxydichotoma-3,14-diene-1,17-dial (ADD, IC50 = 35 µM), isolated from a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In 2014, three different isomers of 2,6‐dolabelladiene and three of 2,8(17)‐dolabelladiene were isolated from the brown alga Dictyota pfaffii and exhibited anti‐​HIV‐​1 activity. Dolabelladienetriol showed strong inhibitory activity against HIV‐1 reverse transcriptase enzyme and was thus deemed as a potential drug for antiretroviral therapy . Pardo‐Vargas et al .…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, three different isomers of 2,6‐dolabelladiene and three of 2,8(17)‐dolabelladiene were isolated from the brown alga Dictyota pfaffii and exhibited anti‐​HIV‐​1 activity. Dolabelladienetriol showed strong inhibitory activity against HIV‐1 reverse transcriptase enzyme and was thus deemed as a potential drug for antiretroviral therapy . Pardo‐Vargas et al .…”
Section: Resultsmentioning
confidence: 99%
“…Researchers also speculate that RT mutations that confer drug resistance, but that are distant from the inhibitor-binding sites, often map to the unique RT-hybrid interface that undergoes conformational changes between the two catalytic states (3). The structureactivity relationship (SAR) of three RT inhibitors of marine origin (THD, HDD, and ADD) was approached with molecular modeling (4). Molecular docking studies of THD into HIV-1 RT wildtype and 12 different mutants showed that mutations have little influence in the positioning and interactions of THD (4).…”
Section: Reverse Transcriptasementioning
confidence: 99%
“…The structureactivity relationship (SAR) of three RT inhibitors of marine origin (THD, HDD, and ADD) was approached with molecular modeling (4). Molecular docking studies of THD into HIV-1 RT wildtype and 12 different mutants showed that mutations have little influence in the positioning and interactions of THD (4). Following a rational drug design approach, a modification of THD was suggested to improve its biological activity (4).…”
Section: Reverse Transcriptasementioning
confidence: 99%
See 1 more Smart Citation
“…The marine natural products produced by these algae are cyclic diterpenes, many exclusive to the marine environment. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The Zika virus (ZIKV) was first isolated in 1947 from the febrile rhesus monkey in the Zika Forest in Uganda. 17 The first case of human infection was originally described in 1954 in Africa after some sporadic infections in humans were recorded.…”
mentioning
confidence: 99%